Removal of anthocyanins from aqueous berry extracts by adsorption on bentonite: Factorial design analysis - Liudmyla Soldatkina; Victoria Novotna (Adsorption Science & Technology)
In this article, a full factorial experimental design 2 4 was used to evaluate four factors (contact time, temperature, initial concentration of anthocyanins, and adsorbent mass) and their interactive effects on adsorption of anthocyanins from elderberry and chokeberry extracts on bentonite. The factors were investigated at two levels (−1 and +1). The regression models considering the main effects and interactions were suggested. The variance analysis and the statistic data showed adequate models. The contact time has the most positive effect and the initial concentration of anthocyanins has the most negative effect that influences the removal of anthocyanins from berry extracts on bentonite.